2006
DOI: 10.1002/bip.20513
|View full text |Cite
|
Sign up to set email alerts
|

Facile preparation of biodegradable chitosan derivative having poly(butylene glycol adipate) side chains

Abstract: Various modes are being explored for the construction of functional materials from nanoparticles. Despite these efforts, the assembly of nanoparticles remains challenging with respect to the requirement of multiple component organization on varying dimensions and length scales. The graft copolymers of chitosan with poly(butylene glycol adipate) (PBGA) were prepared due to the esterification reaction between PBGA and 6-O-succinate-N-phthaloyl-chitosan (PHCSSA) in the presence of toluene as a swelling agent. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…In addition, the new characteristic absorption peaks at 1261 cm -1 and 801cm -1 appeared, which were ascribed to Si-C and Si-O, respectively [16][17][18][19][20]. As shown in Fig.…”
Section: Scheme 1 Reaction Formulas Of Synthesis Of Puismentioning
confidence: 99%
“…In addition, the new characteristic absorption peaks at 1261 cm -1 and 801cm -1 appeared, which were ascribed to Si-C and Si-O, respectively [16][17][18][19][20]. As shown in Fig.…”
Section: Scheme 1 Reaction Formulas Of Synthesis Of Puismentioning
confidence: 99%
“…Hudson et al [11] reported the heterogeneous graft copolymerization of chitosan powder with methyl acrylate using trichloroacetyl-manganese carbonyl co-initiation. Fang et al [12][13][14] prepared the graft copolymers, such as chitosan-g-polyethylene glycol, chitosan-g-poly(vinyl alcohol), and chitosan-g-poly(butylene glycol adipate) by the esterification reaction between 6-O-succinate-N-phthaloyl-chitosan and the synthetic polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Jenkins and Hudson [21] reported the heterogeneous graft copolymerization of chitosan powder with methyl acrylate using trichloroacetyl-manganese carbonyl Co-initiation. Fang and co-workers [22][23][24] prepared the graft copolymers, such as chitosan-g-polyethylene glycol, chitosan-g-poly(vinyl alcohol), and chitosan-g-poly(butylene glycol adipate) by the esterification reaction between 6-O-succinate-N-phthaloyl-chitosan and the synthetic polymers.…”
Section: Introductionmentioning
confidence: 99%